Looking for Carrascolendas : from a child's world to award-winning television - Barrera, Aida (Louann Atkins Temple women & culture series., 2001)
"This award winning show which originally aired on PBS in the 1970 and was subsequently broadcast throughout the country in the 1980s and 1990s, was the first Spanish and English children's educational television program broadcast to national audiences in the United States."